Transcobalamins I and II as natural transport proteins of vitamin B12. - Hall, C A (1975)
There are two conflicting theories of how plasma vitamin B12 (B12) is transported in man: (a) by two distinct transport proteins, transcobalamins I and II (TC I and II), each having a specific role and time of function; and (b) by three active transport proteins, TC I, II, and III, that take up B12 randomly in proportion to the unsaturated amounts of each. To test these theories a man was given 1.12 mug, 229 muCi, of [57Co]B12 mixed with food. Blood samples were taken several times on the 1st day and at lengthening intervals up to day 51. The amount of TC II-B12 was measured in each sample by: gel filtration and by precipitation with (NH4)2SO4. Total serum R-B12 was then separated into TC I and TC III by: (a) a single step anion exchange system and (b) isoelectric focusing (IEF). As the B12 was being absorbed, 92-95% of that in venous blood was carried by TC II. Absolute and percentage transport by TC II declined sharply during the first 24 h; between days 7 and 51 20-33% of the label was on TC II, and the rest was carried by R-type binders. Absolute transport by TC I did not reach a maximum until after day 1 and before day 3. Transport by an alpha2 R-type binder, TC III, could not be demonstrated. TC I was isoelectrically heterogenous, with the components focusing between pH 2.9 and 3.35. It was concluded that (a) TC II is the dominant carrier of B12 immediately after absorption; (b) maximum transport by TC I requires the passage of time after absorption; (c) after the absorbed B12 reaches equilibrium with the total body B12, about one fourth of the plasma B12 is carried by TC II and three fourth by TC I; and (d) TC I and TC II are the only functional transport proteins of plasma B12.